Development of E-Scrapbook Media Containing Hot Listed Questions in Science Subjects - trinadia, dhea; Ida; Suryani, Ida; H.M. Lubis , Patricia (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research was motivated by students' lack of enthusiasm in the learning process, learning that was less interesting because the learning media was less varied, there was a lack of use of technology that existed at the school, teachers rarely related to the water cycle material in the environment around the school. This aim is to produce an E-Scrapbook media product containing hots-based questions in the science subject water cycle material for class V SD Negeri 08 Palembang that is valid, practical and effective. This research uses the Research and Development research method using the ADDIE method (analysis, design, development, implementation and evaluation). The results of this research obtained an average score for media experts of 72% with "valid" criteria, an average score for material experts of 80% with "valid" criteria. Practicality results by the class teacher obtained a score of 90% with the criteria "very valid" while product practicality results by 3 students, and the small group obtained an average score of 88,8% with the criteria "very practical" student learning results with trials the large group obtained a score of 93 with good criteria. So the E-Scrapbook media contains hot-based questions in science subjects that are valid, practical and effective for use in the learning process.